Pulmonary embolism as a complication of fracture of the proximal end of the humerus - literature review - Wokurka, Wojciech; Węgrzyniak, Agata; Dudek, Iga; Piech, Piotr (Journal of Education, Health and Sport, 2021)
Introduction and purpose: Pulmonary embolism (PE) is one of the leading causes of death worldwide. There are many factors that increase the risk of its occurence. High costs of treatment, non-specific symptoms and high mortality of the disease determine the further search for new methods of treatment and diagnostics. The aim of the study is to determine the incidence of PE in patients after fracture of the proximal end of the humerus. Materials and methods: A literature search was conducted in the PubMed MEDLINE database of medical publications using the following keywords: pulmonary embolism, deep vein thrombosis, proximal humerus fracture. Results: Among the found articles, 4 original papers describing the problems of pulmonary embolism after fractures of the proximal end of the humerus were qualified for further analysis. The incidence of PE after this type of fracture is rare and ranges from 1.3% to 5.1%. Moreover, PE was not the cause of death of any patient in the analyzed literature. Conclusion: The need for further randomized controlled trials on a large group of patients operated with the same technique was demonstrated, including subgroups with and without antithrombotic chemoprophylaxis.